The predictors of the likelihood of contacting HIV/AIDS among Kenyan women and the role of tertiary home economics programs in the prevention of the pandemic - Muchee, Tabitha Mumbi (2004)
This study was conducted to determine the predictors of likelihood of contacting HIV/AIDS among Kenyan women and to come up with a Tertiary Home Economics program in the prevention of the pandemic. A total of 350 women; 265 non-HIV and 85 HIV positive, served as the respondents. Also a total of 11 (five administrators and six Home Economics teachers) participated in Focus Group Discussions. The statistical tool used for data gathering were percentages, standard deviation, mean, t-test and regression. Results showed that majority of the respondents were single, religious, social, and were brought up in democratic families. The significant difference between non-HIV and HIV positive was found in terms of age, educational background, personality type, hobbies, residence, family income, parents' occupation and education, family discipline; knowledge and attitude. However there was no significant difference in terms of religion and sexual behavior. The predictors of the likelihood of contacting HIV/AIDS included; religiosity, forced sex, media influence, residence, education attainment, and family discipline. The documents analyzed showed that HIV/AIDS prevention is not included in the Tertiary Home Economics curriculum in Kenya and yet the philosophy states that the program is geared to help rural families maintain their dignity. The results of the FGD was that HIV/AIDS prevention should be incorporated in Home Economics Program and should be made more practical with an aim of reexamining and changing some traditional beliefs which are contributing to the spread of the disease and a hindrance in development and progress of the nation.